Literature review: completeness of filling medical record to the quality of medical record: Literatur review: kelengkapan pengisian rekam medis rawat inap terhadap mutu rekam medis - purwanti, ika setya; Prihatiningsih, Diah (Bali Medika Jurnal, 2021)
Every health facility, whether it is primary, secondary, tertiary, is required to organize medical records in order to achieve administrative order. Completeness of medical records is very important because it affects the service process provided by health workers and has an impact on the quality of service in a hospital. This study aims to determine the completeness of filling in inpatient medical records on the quality of medical records. This study uses a literature review method. Search strategy using Google Scholar. The keywords used were incomplete filling of inpatient medical records and the quality of medical records. Search results obtained 180.000 article according to keywords. Then the article obtained were filtered based on full text and publication date 2015 – 2020, found 44.700 articles. Of the 44.700 articles reviewed related to titles that were deemed appropriate and obtained 18, then these 18 articles were screened based on inclusion and exclusion criteria and obtained 5 articles. As a whole, the cause can be seen from the lack of knowledge, motivation and awareness of medical personnel about medical records. The meeting as a means of communication between caregivers and management has not yet been implemented to discuss evaluation and monitoring as well as sanctions for officers who do not complete medical records. Lack of socialization on filling out medical records. Unsystematic arrangement of medical records forms. Limited availability of funds or budget to support medical record service activities.